Generational perceptions at work: in-group favoritism and out-group stereotypes. Issue 1 (13th February 2017) - Weeks, Kelly Pledger; Weeks, Matthew; Long, Nicolas
Abstract : Purpose: The purpose of this paper is to examine the relationship between stereotypes, in-group favoritism, and in-group bolstering effects across generations. Design/methodology/approach: Based on the trends found in a qualitative study on generational stereotypes, questions on work ethic, work-life balance, and use of technology were administered to 255 participants identified as Millennials, Generation X, and Baby Boomers. Hypotheses predicted that with a strong stereotype, traditional in-group favoritism will not be found; however, an in-group bolstering effect will emerge. In the absence of a strong stereotype, traditional in-group favoritism is expected. Findings: Generally, there was a strong stereotype that Baby Boomers are worse at technology than Generation X and Generation X is worse than Millennials. There was also a strong stereotype that Millennials do not do what it takes to get the job done as much as other generations. In the presence of these stereotypes, traditional in-group favoritism was not found, but in-groups bolstered themselves by rating themselves more favorably than other groups rated them. Although these findings did not hold for every item studied, there was moderate support for all three hypotheses. Practical implications: As employees become aware of their biases, they can collaborate better with employees who are different than they are. Practical recommendations are suggested. Originality/value: The paper applies theory of in-group favoritism to the perceptions of generational cohorts.